PENGARUH KESEHATAN DAN KESELAMATAN KERJA ( K3 ) DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT RICKSTAR INDONESIA - Catur Hadi Prabowo; Widodo (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
This research aims to analyze the influence of occupational health and safety and the work environment against work productivity of employees of PT (limited liability company) Rickstar Indonesia. The population used in this research were part of the production of PT (limited liability company) Rickstar Indonesia as many as 50 employees with sampling techniques using simple random sampling and data analysis techniques using analysis multiple linear regression. The results showed that there was influence of occupational health and safety and the work environment against work productivity of employees of PT (limited liability company) Rickstar Indonesia.